Improving Children's Gross Motor Development Through Indang Dance Movements - Naifwan, Rini; Susanto, Rezi; Sarmita, Dian; Yenti, Yesni (Strata International Journal of Social Issues, 2024)
This research was motivated by children's low gross motor development, including the following. First, children like to run around without rules, so injuries often occur to themselves and their friends. Second, the child's lack of interest in being active. Third, teachers have not found the proper method for creating exciting learning activities for children. Fourth, the child does not want to do dance movements. Shows that the child's gross motor development condition is deficient. Based on this, the researchers implemented dancing activities. This research aims to improve children's gross motor development. This type of research is Classroom Action Research (PTK). The subjects of this research were group B children, which consisted of 12 children from Dharma Wanita Lubuk Gadang Kindergarten, Sangir District, South Solok Regency. This research was carried out in two cycles, each with 2 meetings. The stages in this research are planning, action, observation, and reflection. There was an increase in children's gross motor development from cycle I to cycle II. In cycle I, meeting 1, the increase in children's gross motor development was 55.5%, and 74.9% in meeting 2. In cycle II, meeting 1, the increase in children's gross motor development was 83.3%, and 88.8% in meeting 2. Classroom Action Research using activities dancing has worked out well. Implementing learning with dancing activities can also train children's gross motor development well.